Studies in law, politics and society. Vol. 38 - Sarat, Austin (Elsevier JAI, 2006)
This volume of "Studies in Law, Politics, and Society" presents a diverse array of articles by an interdisciplinary group of scholars. Their work covers several social science disciplines as well as law. Some of the articles published in this issue examine the interactions of law and "vulnerable" populations. Here research illustrates the complex ways law can be used by those groups, as well as the impact of law on their lives. Other articles focus on indigenous groups and particular legal controversies in which they are involved. Taken together they exemplify the exciting and innovative work now being done in interdisciplinary legal scholarship.